Analytical Method for Investigation of Three-phase Converter Systems in Steady State Operation based on Space Phasors - Herold, Gerhard (2008 Power Quality and Supply Reliability, 2008)
A method for analytical calculation of pha-se-commutated converters based on space phasors is pre-sented. For it the steady state operation of the converters is considered as a periodical sequence of transient swit-ching processes. The order of the state space of the sCS is not limited belonging to the computation, but it is limited surely belonging to the interpretation of the computatio-nal results. The method can be used for investigation of extreme and optimum operating points as well. It deli-vers all of the factors to describe power quality. 3-phase ac systems with FACTS equipment (Flexible AC Trans-mission Systems) based on thyristors are of the 6pulse type also. They can calculated by using this method as well. © 2008 IEEE.
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.leen.analyt